The Effect of Perceived Price, Service Quality, and Trust on Customer Satisfaction - Amanda, Sonia Dwita; Prameka, Adelia Shabrina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research aims to discover the effect of perceived price, service quality, and trust on customer satisfaction for students who use Maxim online transportation. The type of this research is the explanatory research which explains the relationship and the influence between one variable and another through hypothesis testing. The samples of this research consist of 120 individual respondents. Furthermore, the respondents are the students at Malang University who knew, used, and made repeated purchases from Maxim online transportation. Thus, this research uses a sampling technique with a non-probability sampling method by applying a purposive sampling technique. The hypothesis testing is carried out to determine the influence between variables. The data were analyzed using The Statistical Package for Social Sciences (SPSS) 25. The results of this study indicate that perceived price, service quality, and trust have a positive influence on customer satisfaction on Maxim online transportation users. So if perceived price, service quality, and trust get better, customer satisfaction for Maxim users will also get better. The results of this research can help the Maxim company to optimize its marketing strategy by paying attention to factors such as perceived price, service quality and trust.